Spatial Assessment of Selangor, Malaysia Water Treatment Plant Performance Using Chemometric Technique - M. Zolkipli, H; Juahir, H; Adiana, G; Zainuddin, N; B. H. M. Maliki, A; E. Toriman, M; Mokhtar, M; Elfitri, R (International Journal of Engineering and Technology, 2018)
This study aims to identify the most significant parameters in drinking water quality, spatial disparities of treated water (TW) and performance of water treatment plant (WTP) in Selangor. Physico- chemical (PCPs), Inorganic (IPs), Heavy metal and organic (HMOPs) and pesticide (PPs) were selected as parameters to discriminate the source of WTP pollutant. Chemometric technique such as principle component analysis (PCA), one-way analysis of variance (ANOVA) and discriminant analysis (DA) was applied to validate the performance of water treatment plant. PCA identified the most significant parameters which are highlighted six out of eight parameters for PCPs, six out of twelve parameters for IPs, nine out of sixteen parameters for HMOPs and all seventh parameters for PP. ANOVA for distinguish two categories region in WTP and showed both of PCPs and IPs had significant differences due to their concentration (p < 0.5) and HMOPs suggested fifth of significant differences within regions (p < 0.05). PP doesnâ€™t give any significant differences (p > 0.05). DA was suggested PCPs, IPs and HMOPs in good performance (76.96%, 91.90% and 93.27%) except PP (50.43%). We can conclude that this chemometric technique can expose which area of WTP need to be properly maintains their performance to produce high quality of drinking water.Â Â